"The Marriage of Figaro" - Dias, Robert (Temple University. Office of University Relations (Philadelphia, Pa.), 1984)
"Therese Boyle Greenland, as Susanna, bows to Mark Gargiulo, as Count Almaviva and Marilyn Moore as the Countess in Temple's production of Mozart's 'The Marriage of Figaro.'"